Influence of donor KIR genotypes on reduced relapse risk in acute myelogenous leukemia after hematopoietic stem cell transplantation in patients with CMV reactivation. (December 2019) - Nakamura, Ryotaro; Gendzekhadze, Ketevan; Palmer, Joycelynne; Tsai, Ni-Chun; Mokhtari, Sally; Forman, Stephen J.; Zaia, John A.; Senitzer, David; Marcucci, Guido; Stein, Anthony
Highlights: The incidence of AML relapse is reduced with CMV reactivation. NK cells are involved in CMV-associated protection from AML relapse. CMV infection trigger/enhance a response by NK expressing activating KIRs. Abstract: Multiple retrospective studies have demonstrated an association between cytomegalovirus (CMV) reactivation and reduced risk of AML relapse. However, the potential mechanism explaining this association remains elusive. We investigated a homogeneous cohort of 288 adult patients with AML in remission who received allogeneic hematopoietic stem cell transplantation (HCT) from matched sibling/unrelated donors between 1995 and 2011. The 5-year cumulative incidence of relapse was greater in patients without CMV reactivation compared with those with reactivation (30.2% vs. 12.1%, p = 0.001) in a landmark analysis. In multivariate analyses CMV reactivation was independently associated with reduced relapse risk (HR: 0.49 [0.25-0.95], p = 0.036) and increased non-relapse mortality (26.5% vs. 13.1%, p = 0.002) resulting in similar 5-year overall survival (64.5% vs. 59.1%, p = 0.8). In further subgroup analyses the protective effect of CMV reactivation was significant in patients who received HCT from donors with KIR Bx compared to KIR AA (11.7% vs. 29.5%, p = 0.01). Likewise, the protective effect of CMV reactivation was more significant when the donors had 2DS1 activating KIR (11.5% vs. 30.7%, p = 0.05) compared with those without 2DS1 (14.3% vs. 27.5%, p = 0.12). Our data independently confirmed the association between CMV reactivation and AML relapse, suggesting the involvement of donor KIR genotypes and NK cell-mediated graft-versus-leukemia effect.